2015
DOI: 10.1186/s12859-015-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient representation of uncertainty in multiple sequence alignments using directed acyclic graphs

Abstract: BackgroundA standard procedure in many areas of bioinformatics is to use a single multiple sequence alignment (MSA) as the basis for various types of analysis. However, downstream results may be highly sensitive to the alignment used, and neglecting the uncertainty in the alignment can lead to significant bias in the resulting inference. In recent years, a number of approaches have been developed for probabilistic sampling of alignments, rather than simply generating a single optimum. However, this type of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 123 publications
0
18
0
Order By: Relevance
“…The impact of multiple sequence alignment on downstream analyses is known to be substantial, with errors in multiple sequence alignment producing increased error rates in phylogeny estimation, false detection of positive selection, difficulties in detecting active sites in proteins, etc. [5]. Thus, highly accurate multiple sequence alignment, especially of large datasets spanning large evolutionary distances, is one of the major outstanding bioinformatics problems [6].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of multiple sequence alignment on downstream analyses is known to be substantial, with errors in multiple sequence alignment producing increased error rates in phylogeny estimation, false detection of positive selection, difficulties in detecting active sites in proteins, etc. [5]. Thus, highly accurate multiple sequence alignment, especially of large datasets spanning large evolutionary distances, is one of the major outstanding bioinformatics problems [6].…”
Section: Introductionmentioning
confidence: 99%
“…These are expected to be more accurate, but generally take much longer. MCMC samplers may be usefully supplemented by decisiontheoretic approaches to summarize a sampling run (Herman et al, 2015). Other potential ways to improve accuracy include context-dependent gap penalties, as used by Muscle (Edgar, 2004), and explicit modeling of tandem duplications (Szalkowski and Anisimova, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Applying this process will help the WSS utility manager (or decision-makers) reconcile short-and long-term priorities, and make decisions to increase the utility's resilience, despite deep uncertainties about future conditions (be these related to climate, demand, or budget). For instance, it has been used to integrate long-term infrastructure investments, near-term operational strategies, and medium-term financial instruments (Herman et al 2015).…”
Section: Chaptermentioning
confidence: 99%
“…and analysts must select those that are robust to deep uncertainties or adaptable to a changing future. A review of methodologies can be found inHerman et al (2015) andDittrich, Wreford, and Moran (2016). For instance, decision scaling(Brown et al 2012) uses a weather generator to stress-test water projects against a wide range of future climate and hydrological conditions and adapt them so that they perform well in a large number of scenarios.…”
mentioning
confidence: 99%